2022
DOI: 10.3389/fphar.2022.857060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA Damage Response and Repair-Related Gene-Pair Signature for Prognosis Stratification Analysis in Hepatocellular Carcinoma

Abstract: Background: Nowadays, although the cause of hepatocellular carcinoma (HCC) mortality and recurrence remains at a high level, the 5-year survival rate is still very low. The DNA damage response and repair (DDR) pathway may affect HCC patients’ survival by influencing tumor development and therapeutic response. It is necessary to identify a prognostic DDR-related gene signature to predict the outcome of patients.Methods: Level 3 mRNA expression and clinical information were extracted from the TCGA website. The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have detected similar molecular classes. Most studies emphasized two main groups based on the DNA repair genes’ RNA expression [ 8 , 12 , 13 , 60 ]. Three previous studies identified two DNA repair groups: Oshi et al found low- and high-repair groups based on a gene set that included 150 genes [ 12 ]; Lin et al classified DNA-repair-activated and -suppressed groups using 276 genes [ 13 ]; and Chen et al found low- and high-risk DNA repair groups based on 23 DDR-related gene pairs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have detected similar molecular classes. Most studies emphasized two main groups based on the DNA repair genes’ RNA expression [ 8 , 12 , 13 , 60 ]. Three previous studies identified two DNA repair groups: Oshi et al found low- and high-repair groups based on a gene set that included 150 genes [ 12 ]; Lin et al classified DNA-repair-activated and -suppressed groups using 276 genes [ 13 ]; and Chen et al found low- and high-risk DNA repair groups based on 23 DDR-related gene pairs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies emphasized two main groups based on the DNA repair genes’ RNA expression [ 8 , 12 , 13 , 60 ]. Three previous studies identified two DNA repair groups: Oshi et al found low- and high-repair groups based on a gene set that included 150 genes [ 12 ]; Lin et al classified DNA-repair-activated and -suppressed groups using 276 genes [ 13 ]; and Chen et al found low- and high-risk DNA repair groups based on 23 DDR-related gene pairs [ 60 ]. Across these studies, similar to our results, the high-repair-activated samples were associated with worse survival, and these authors further found that high-repair-/DDR-activated samples were associated with distinct immune profiles, poor differentiation, elevated intratumor heterogeneity, and mutation burden.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the crucial role of the DDR process in regulating the biological behavior and therapeutic susceptibility of tumor cells (69). Risk models based on DDRrelated genes have been constructed for different cancers, such as lung adenocarcinoma (LUAD), hepatocellular carcinoma (HCC), and soft tissue sarcoma, with many studies focusing exclusively on the prognostic value of the models (70)(71)(72). However, DDR-related lncRNAs have received less attention in GC research.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Apart form TNM stage, the pre-EBV DNA, reflecting tumor burden, has emerged as a significant factor in the clinical diagnosis, risk classification, dynamic monitoring, and prognosis of NPC patients, serving as an important a supplement for the TNM staging system. 20 , 21 Patients with higher pre-EBV DNA copy numbers appear to have a greater risk of distant metastasis, necessitating more aggressive treatment. Nevertheless, these considerations often overlook the impact of hematological parameters on the treatment of NPC patients, potentially affecting treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%